Politics of forced migration and refugees: Dynamics of international conspiracy? - Moniruzzaman, Md. (2017)
Human mass migration from place to place is well recorded in history. The ancient patterns of mass migrations could have their origins in natural force (Homo-erectus from Africa to Europe) or divine order (Israelites from the Pharaonic Egypt or early Muslims from Makkah). Simultaneously, from ancient times human mass migrations were triggered by local and regional politics too such as political oppression (Nazi holocaust, Israeli occupation) or imperial invasion. However, a new pattern of mass migration emerged with the 20th century triggered by a complete new force- strategic redrawing of certain regional maps. This strategic redrawing of maps is not locally inspired but imposed from abroad as part of competitive economic and military strategies on a global scale. This article intends to analyze the mass migrations triggered by Iraq-Syria civil wars in the framework of international strategic global competition. The article argues that these mass migrations are artificially caused by the economic and military strategies of international hegemonic powers. Strategic national interest abroad is the underlying objective at the cost of the sufferings of the millions.